Perception of Body Image Related to Nutritional Status of Young Women in Pontianak City During the Covid-19 Pandemic - Deviro Deviro; Tonang Dwi Ardyanto; Anik Lestari (Universitas Aisyah Pringsewu, 2023)
Covid 19 is a pandemic disease experienced throughout the world. This pandemic causes limitations on activities outside the home so it will impact the health and mentality of adolescents. Adolescent girls are in a period of transition from children to adults. Adolescence is an age that is very vulnerable to nutritional problems, this is caused by a lack of self-confidence, lifestyle, and knowledge of balanced nutrition. Often, young women feel dissatisfied with their body shape, so they go on a diet to get the desired body shape. This study aimed to determine the relationship between body image and nutritional status in young women during the Covid 19 pandemic in Pontianak City. This research is an observational study with a cross-sectional design chosen randomly and then the Pontianak Health Polytechnic, Stikes Yarsi, and Aisyiyah Polytechnic were selected. The sample in the study was 102 female students using sampling using proportional random sampling. Data collection was carried out in March-April 2022. The data collection technique measured the waist-hip ratio (RLPP) and used a figure rating scale questionnaire with a Cronbach alpha of 0.85. Then the data were analyzed using the chi-square test with a 95% confidence level. The results of this study indicate that 76 respondents (74.5%) have a negative body image and 26 respondents (25.5%) have a positive body image. In comparison, regarding the nutritional status of young women 74 respondents (72.5%) were obese and 28 respondents (27.5%) were not obese. The chi-square test results were obtained with p = 0.00 (p less than 0.05). This shows a relationship between body image and the nutritional status of young women in Pontianak City during the Covid 19 pandemic. Young women who experience nutritional status obesity tend to have a negative body image compared to young women whose nutritional status is not obese tend to have a positive body image. Abstrak: Covid 19 merupakan penyakit pandemi yang dialami seluruh dunia. Pandemi ini menyebabkan keterbatasan kegiatan diluar dirumah sehingga akan berdampak kesehatan dan mental pada remaja. Remaja putri merupakan masa peralihan dari anak-anak ke dewasa. Usia remaja merupakan usia yang sangat rentan terhadap permasalahan gizi hal tersebut diakibatkan oleh kurang kepercayaan diri, gaya hidup serta kurangnya pengetahuan gizi seimbang. Seringkali remaja putri memiliki rasa ketidakpuasaan terhadap bentuk tubuhnya sehingga remaja akan melakukan diet untuk mendapatkan bentuk tubuh yang diinginkan. Tujuan Penelitian ini adalah untuk mengetahui hubungan body image dengan status gizi pada remaja putri selama masa pandemi covid 19 di Kota Pontianak. Penelitian ini merupakan penelitian observasional dengan desain cross sectional yang dipilih secara random kemudian terpilih politeknik kesehatan Pontianak, stikes yarsi dan politeknik aisyiyah. sampel pada penelitian sebanyak 102 mahasiswa putri dengan cara pengambilan sampelnya menggunakan proportional random sampling. Pengambilan data dilakukan di bulan maret-april 2022. Teknik pengumpulan data menggunakan perngukuran rasio lingkar pinggang-panggul (RLPP) dan menggunakan kuesioner figure rating scale dengan alpha cronbach sebesar 0,85. Kemudian data dianalisis menggunakan uji chi-square dengan tingkat kepercayaan 95%. Hasil dari penelitian ini menunjukkan bahwa sebanyaj 76 responden ( 74,5%) mempunyai body image negatif dan 26 responden (25,5%) memiliki body image positif, sedangkan status gizi pada remaja putri sebanyak 74 responden (72,5%) obesitas dan 28 responden (27,5%) tidak obesitas. Hasil dari uji chi-square diperoleh dengan nilai p=0,00 (p kurang dari 0,05). Hal tersebut menunjukkan bahwa ada hubungan body image dengan status gizi remaja putri di Kota Pontianak selama masa pandemi covid 19. Remaja putri yang mengalami status gizi obesitas cenderung memiliki body image negatif dibandingkan remaja putri yang status gizinya tidak obesitas cenderung memiliki body image positif.